Operationalising urban sustainability: defining, measuring and modelling. - Purvis, Ben (2020)
Despite its ubiquity urban sustainability is a contested concept with no widely accepted definition of what it is, or what it should look like. This lack of consensus surrounding meaning presents barriers to coherent operationalisation to bring about positive change, leading to the dominance of undertheorised indicator based approaches. Such approaches present various issues including the marginalisation of less quantifiable aspects, and the erasure of holism and interaction between relevant phenomena. This thesis seeks to develop a deeper understanding of urban sustainability, and how it can be operationalised to explore coherent ways of improving upon it.